The Impact of Gamification and Individual Differences on Second Language Learning Among First-Year Female University Students in Saudi Arabia. (December 2021) - Almufareh, Maram
Background: The Technology-Enhanced Training Effectiveness Model (TETEM) has been used to assess the effectiveness of various technology-driven solutions in improving students' outcomes in multiple academic fields. However, limited research is available on the use of TETEM in the context of second language learning. Using a modified TETEM, this study seeks first, to assess the direct effects of students' attitudes and experiences with video gaming on their achievement; and second, to evaluate the effects of students' attitudes and experiences that are mediated by their motivation. Methods: This study was conducted among preparatory year students at Al-Jouf University, Saudi Arabia. Students were randomly assigned to the technology-enhanced group (Duolingo® + workbook) or the control group (classroom workbook group). We started by comparing student performance between the two groups to evaluate the effect of the intervention. Subsequently, we conducted a confirmatory factor analysis to establish homogenous latent variables for experience, attitude, and motivation. Finally, we used structural equation models to evaluate the presence of direct and mediated effects. Results: Students in the Duolingo® + workbook group scored higher on reading, grammar, vocabulary, and writing compared to the workbook group. Positive attitude toward video gaming had both a direct and mediating positive correlation with student achievement. Additionally, motivation toward ESL learning was independently and positively correlated with student achievement. As expected, the technology-enhanced group performed better in reading, grammar, and vocabulary while the control group showed more participation and timely completion of assignments. Conclusion: Technology enhancement improves students' performance for ESL, however, adequate integration of technology in the course curriculum is needed to minimize interference with class participation. Positive attitudes toward video games and motivation toward ESL learning are positive predictors of student achievement while experience with video games has no significant effect.